Penerapan Teknik TEGAR (Teguran dan Positive Reinforcement) untuk Mengurangi Perilaku Impulsif pada Anak dengan Attention-Deficit Hiperactivity Disorder (ADHD) - Ruwita Erinasari; Defi Astriani; Wiwik Suatin; Alaiya Choiril Mufidah (Universitas Islam Tribakti Lirboyo Kediri, 2024)
ADHD children have problems with impulsive behavior, namely snatching and taking other people's things without permission. This makes it difficult for children to adapt to their environment, making it difficult to make friends. So this impulsive behavior must be reduced. This research intervention uses the TEGAR (Teguran and Positive Reinforcement) technique. This research aims to reduce the impulsive behavior of children with ADHD. The application of the TEGAR technique (Teguran and Positive Reinforcement) is a combination of Reprimand and Positive Reinforcement techniques, where children are given a warning when they show impulsive behavior. After the child displays the desired behavior, the child is immediately given Positive Reinforcement in the form of praise. The research method used was quasi-experimental with a one-group pretest-posttest design. The research subjects were 6 children with ADHD. The research used a pretest scale before being given treatment and a protest scale after being given treatment which was tested using IBM SPSS 26.0 for Windows non-parametric method with the Wilcoxon test. The test results showed that there was a change in behavior before and after being given treatment using the TEGAR technique (Teguran and Positive Reinforcement) but it was not significant (Z = -1.261, p = 0.207 (p < 0.05)). So it can be concluded that the application of the TEGAR (Teguran and Positive Reinforcement) technique can reduce impulsive behavior in children with ADHD.